Penerapan Model Contextual Teaching and Learning terhadap Pembelajaran Tematik - Ranty Septria Putri; Asep Sukenda Egok; Riduan Febriandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the completion of thematic learning outcomes in the science content of the fifth grade students of Sukadana State Elementery School. The method used is the experimental method with one group pretes posttes design. This study uses 1 sample class, namely class V with 19 students. This means that all members of the population are sampled. Data collection is carried out with saturated sampling technique. The instrument used by the researcher ia in the form of essay questions, totaling 7 questions. The z-test formula based on the results of the data analysis test with a confidence level 5% shows = 10,71 and . Because > . With that, it can be concluded that the thematic learning outcomes in the fifth grade science content at the Sukadana State Elementary School after the application of the Contextual Teaching and Learning (CTL) model to the thematic learning outcomes in the fifth grade science content at the Sukadana State Elementary School ware significantly completed. Keywords. Contextual teaching and learning (CTL) learning model, thematic learning outcomesof science content.